TRAINING AIR TRANSPORT TECHNOLOGIES SPECIALISTS: FOREIGN EXPERIENCE - Akmaldinova, Oleksandra; Akmaldinova, Viktoriia; Volkovska, Hanna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article is devoted to analysing the system of professional training of future specialists in air transport technologies in foreign higher technical education experience. The purpose of the article is to highlight the peculiarities of foreign experience in the formation of future aviation industry engineers professional competences under the influence of scientific and technical progress. Examples of aviation specialists theoretical and practical training in higher education institutions of the USA, Great Britain and the member-states of the European Union based on the use of innovative problem-oriented, distance and mixed learning methods, fruitful cooperation with stakeholders, taking into account the autonomy of educational institutions and the educational system flexibility are given. Theoretical and empirical methods of comparative and generalizing analysis of different level academic programs (Bachelor’s & Master’s) and aviation specialists training experience have been used in the research. Results.The system of the USA future pilots professional training effectively combines theoretical and practical types of activities, intensive use of computer technologies in the training process significantly improving its quality and effectiveness. According to the bachelor’s and master’s programs in aeronautical engineering presented by Great Britain higher technical education institutions, the training content involves an in-depth study of the flight practice basics and subjects of the professional orientation. The professional training of future specialists in air transport technologies in higher educational institutions of Germany is focused on integrated studying, practical training, internships and advanced training in airlines. The analysis of the international experience of future specialists in air transport technologies professional training shows that the characteristic features of training are the mandatory combination of theory and practice, with special emphasis on the professionally-oriented subjects in educational and professional programs, academic curricula, sufficient number of training hours for practice and internship in order to increase the future specialists competitiveness and attract experienced aviation experts to participate in the educational process. Conclusion. Thus, it was concluded that in higher technical education institutions of EU member states (Germany, France, Poland), USA and Great Britain, the content of future specialists in air transport technologies professional training is based on the relevant educational standards implemented in educational and professional training programs involving the inclusion of practice-oriented academic subjects. It should be noted that the educational process of training air transport technologies specialists in higher technical education institutions of foreign countries is based on the application of traditional and rationalistic models as well as the developmental training model.